2012
DOI: 10.1016/j.diff.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The development of cervical and vaginal adenosis as a result of diethylstilbestrol exposure in utero

Abstract: Exposure to exogenous hormones during development can result in permanent health problems. In utero exposure to diethylstilbestrol (DES) is probably the most well documented case in human history. DES, an orally active synthetic estrogen, was believed to prevent adverse pregnancy outcome and thus was routinely given to selected pregnant women from the 1940s to the 1960s. It has been estimated that 5 million pregnant women worldwide were prescribed with DES during this period. In the early 1970s, vaginal clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 87 publications
0
41
0
Order By: Relevance
“…The drug was initially FDA-approved for the treatment of vaginitis, postmenopausal symptoms, and postpartum lactation suppression. 23,24 In the early 1940s, literature published by Smith et al 25,26 suggested that estrogen deficiency was responsible for miscarriage and that DES administration during pregnancy decreased fetal mortality. This report prompted off-label prescribing of DES by physicians to pregnant women with high-risk features (eg, previous miscarriages, diabetes, a history of gynecologic surgical procedures) for the prevention of miscarriage.…”
Section: Diethylstilbestrolmentioning
confidence: 99%
“…The drug was initially FDA-approved for the treatment of vaginitis, postmenopausal symptoms, and postpartum lactation suppression. 23,24 In the early 1940s, literature published by Smith et al 25,26 suggested that estrogen deficiency was responsible for miscarriage and that DES administration during pregnancy decreased fetal mortality. This report prompted off-label prescribing of DES by physicians to pregnant women with high-risk features (eg, previous miscarriages, diabetes, a history of gynecologic surgical procedures) for the prevention of miscarriage.…”
Section: Diethylstilbestrolmentioning
confidence: 99%
“…Clear Cell Carcinoma (CCC) is most commonly associated with the neoplasms of the female genital tract, some of which are famously associated with in utero exposure to diethylstilbestrol (DES) [1]. However, CCC can rarely be seen arising from the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…These observations would seemingly suggest that in utero exposure to DES might be at least partly responsible for the observed incidence pattern of AC of the cervix, although we note that there were only 66 cases of CCA (∼2.8%) in the study and this particular subtype has been reported to have the strongest association with DES exposure in epidemiologic studies. It has been suggested that genomic instability may be an important mechanism of DES-induced carcinogenesis (Boyd et al , 1996) and animal experiments have suggested that DES disrupts TRP63 expression in mice and induces adenosis lesions in the cervix and vagina (Laronda et al , 2012). …”
Section: Discussionmentioning
confidence: 99%